(untitled) (Journal of Information Technologies in Education (ITE), 2019)
Learning programming in secondary school or on first university years may facilitate making mathematical or physical problem “alive”. With this in view, we are looking for such tasks for programming that are attractive to them, sufficiently easy but employed important and feasible mathematics and physics. A project has been suggested (several lessons and home works) how to create a MATLABprogram of analogue watch on the computer screen that pursues several educational aims. Initially, students are to split the whole task to several simpler ones that they are able to program. To solve them, students employ plotting graphs, trigonometry and analytical geometry, physical consideration and mental experiment, look for empirical equation to fit data, complete everything with rather easy programming and enjoy finally with pleasant widget on computer screen. Programs are given with comments. They serve, at the time, as an introduction to MATLAB. It may be seen that its environment do not hidden the sense of the work but rather facilitates it. That is why it is suggested for wide use in Ukrainian education.